Gambaran Pengelolaan Limbah Medis Padat pada Klinik Bidan Praktik Mandiri di Kecamatan Lempuing Kabupaten Ogan Komering Ilir Tahun 2023 - Alifta Nursafira; Kamsul, Kamsul; Esti Sri Ananingsih; Faiza Yuniati; Intan Kumalasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
WHO said that in 2010, unsafe injections still caused as many as 33,800 new HIV infections, 1.7 million hepatitis B infections, and 315,000 hepatitis C infections. Independent Practice Midwife Clinics are one source of solid medical waste generation. Knowledge of solid medical waste management at independent practicing midwife clinics in Lempuing District, Ogan Komering Ilir Regency in 2023. Research This type of research is descriptive research. This research was conducted in March-May 2023. The population in this study were all 38 independent practicing midwife clinics. The sample is total sampling, namely all independent practicing midwife clinics. The data collection tool is a checklist sheet. Variable sorting, container, storage, and transportation. Data analysis using Univariate Analysis. Sorting 38 (100%) fulfilled the requirements, containers for labeling infectious waste 8 (22%) and pharmaceutical 13 (44%), container grouping for infectious 15 (40%) and pharmaceutical 30 (70%) did not meet the requirements. Storage contained 23 (59%) separate rooms, 8 (21%) covered packaging, and 20 (53%) identity labeled packaging did not meet the requirements. Transportation 11 (29%) did not carry out transportation. by concluding that 38 (100%) have done proper sorting, for containers that have not been labeled infectious waste 8 (22%) and pharmaceutical 13 (44%), there is no separate storage room 23 (59%), there is the packaging does not have a cover 8 (21%), the packaging does not have an identity label 20 (53%). Transportation 11 (29%) did not carry out the transportation be consistent in carrying out proper sorting, more complete facilities, especially in terms of container and storage, and know how to process and transport medical waste properly and correctly.